The Green Building Index (GBI): an innovation in landscape architecture - Nizarudin, Norhanis Diyana; Mohd. Hussain, Mohd. Ramzi; Tukiman, Izawati (2011)

(untitled)
This paper presents a review of the Green Building Index as a new innovation in landscape architecture scope of works. The Green Building Index (GBI) is a green rating system introduced by the Pertubuhan Arkitek Malaysia (PAM) to evaluate the performance of building across a broad range of environmental considerations. Apart from evaluating the building’s performance, the landscape design aspect has become a major part and parcel from the overall GBI assessment through the criteria of open spaces, landscaping and heat island effect. The paper is intend to highlight the important role played by the landscape architects to conserve natural area, encourage restoration of the habitat as well as maximise the ecodiversity through native and adaptive vegetation. It is hoped that GBI may possibly be a new innovation and added-value to espouse landscape architecture field as a leading role together with the architecture and other components in built environment industry.